2020
DOI: 10.3390/microorganisms8020295
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Transcriptional Profiles of Human Stem Cell-Derived β Cells Following Enteroviral Challenge

Abstract: Enteroviral infections are implicated in islet autoimmunity and type 1 diabetes (T1D) pathogenesis. Significant β-cell stress and damage occur with viral infection, leading to cells that are dysfunctional and vulnerable to destruction. Human stem cell-derived β (SC-β) cells are insulin-producing cell clusters that closely resemble native β cells. To better understand the events precipitated by enteroviral infection of β cells, we investigated transcriptional and proteomic changes in SC-β cells challenged with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Using quantitative RT–PCR, we found that the Ct values of Tet 1, 2, 3 were approximately 25, 23, and 26, respectively, against the Ct value of approximately 15 for β-ACT (data not shown). The expression of Tet was also supported by other studies using primary human islets as well stem cell–differentiated beta cells ( 17 , 18 , 19 ). Following a 24-h proinflammatory cytokine exposure, the expression of DNMTs DNMT1 ( p = 0.22, n = 9), DNMT3a ( p = 0.057, n = 11), DNMT3b ( p = 0.18, n = 7), Tet2 ( p = 0.4796, n = 12), and TDG ( p = 0.36, n = 6) did not change, but the expression of Tet1 and Tet3 was significantly reduced ( p = 0.0006, n = 10 and p = 0.0006, n = 10, respectively, Fig.…”
Section: Resultssupporting
confidence: 68%
“…Using quantitative RT–PCR, we found that the Ct values of Tet 1, 2, 3 were approximately 25, 23, and 26, respectively, against the Ct value of approximately 15 for β-ACT (data not shown). The expression of Tet was also supported by other studies using primary human islets as well stem cell–differentiated beta cells ( 17 , 18 , 19 ). Following a 24-h proinflammatory cytokine exposure, the expression of DNMTs DNMT1 ( p = 0.22, n = 9), DNMT3a ( p = 0.057, n = 11), DNMT3b ( p = 0.18, n = 7), Tet2 ( p = 0.4796, n = 12), and TDG ( p = 0.36, n = 6) did not change, but the expression of Tet1 and Tet3 was significantly reduced ( p = 0.0006, n = 10 and p = 0.0006, n = 10, respectively, Fig.…”
Section: Resultssupporting
confidence: 68%
“…Previous studies of acute enteroviral infection showed that: (a) cultured neural cells infected with CBV3 had enhanced secretion of IL6, IL8, and MCP1 and the upregulation of SOCS3, a suppressor of cytokine signaling [ 26 ]; (b) human pancreatic islets infected with CVB3 and CVB4 secreted high amounts of IL6, IL8, MIP-alpha and -beta, and TNF; (c) human pancreatic beta cells infected with CBV4 showed the activation of innate immune pathways including the expression of IFN (alpha, beta, lambda), IL6, IL8, and IL27 and also showed a defective insulin response to glucose [ 35 ]; (d) patients with hand-foot-and-mouth disease caused by EV-A71 and EV-A6 had significantly increased serum levels of IL5, IL7, IL13, IL16, IL18, IP10, NGF-beta, PDGF-beta, and TGFB1 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another important discovery favouring enteroviral β-cell tropism was specific β-cell intracellular factors that the virus can hijack for successful infection and replication in β-cells [77]. At the same time, β-cells are thought to upregulate a range of anti-viral proteins in response to an interferon encounter [77,101]. Furthermore, risk-associated genetic variants found in susceptible individuals are associated either with altered interferon responses [77,98,100,102], impairment of the virus clearance, or inducement of the cytokine storm and destruction of β-cells, substantiating the possible role of viruses in initiating the diabetogenic process [58].…”
Section: Viral Infectionsmentioning
confidence: 99%
“…It was also demonstrated that viral particles spread to neighbouring sites via extracellular vesicles, thus evading immune responses from the host [103]. This suggests that a prolonged low-grade infection of β-cells, owing to defective antiviral resistance, triggers the presentation of both β-cell and viral antigens at the cell surface, a potentiated inflammatory response, β-cell damage, and autoantigen release [77,100,101].…”
Section: Viral Infectionsmentioning
confidence: 99%